Primary intraosseous glomus tumor: A case report - Settakorn J. (2014)
We reported a rare case of a primary intraosseous glomus tumor in a 53-year-old woman who had a small lytic lesion in the distal phalanx of her left index finger. The radiologic appearance showed a well circumscribed osteolytic lesion without sclerotic rim. Histologic examination revealed solid nests or sheets of polygonal cells surrounding branching vasculatures consistent with a glomus tumor. Curettage resulted in complete removal of the tumor as well as pain alleviation. The patient was well without evidence of recurrent disease following an 18 month follow-up. Despite its rarity, intraosseous glomus tumor should be included in the differential diagnosis of bone lesions in which plain radiography showed a well circumscribed punch-out lesion without sclerotic rim especially those arising in the finger.